2015
DOI: 10.1159/000369068
|View full text |Cite
|
Sign up to set email alerts
|

Inhalation of Hydrogen Gas Is Beneficial for Preventing Contrast-Induced Acute Kidney Injury in Rats

Abstract: Background: The present study aimed at investigating the effect of a novel antioxidant, hydrogen (H2) gas, on the severity of contrast-induced acute kidney injury (CIAKI) in a rat model. Methods: CIAKI was induced in rats by intravenous injection of a contrast medium, Ioversol, in addition to reagents inhibiting prostaglandin and nitric oxide synthesis. During the injection of these reagents, the rats inhaled H2 gas or control gas. Results: One day after the injection, serum levels of ure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 25 publications
2
19
0
Order By: Relevance
“…We also observed tubular epithelial necrosis by microscopic detection, similar to other studies on AKI caused by different reasons [3133]. Applied HS, less necrotic tubules were found with a lower tubular damage score, which suggests a relief of early AKI post burn.…”
Section: Discussionsupporting
confidence: 89%
“…We also observed tubular epithelial necrosis by microscopic detection, similar to other studies on AKI caused by different reasons [3133]. Applied HS, less necrotic tubules were found with a lower tubular damage score, which suggests a relief of early AKI post burn.…”
Section: Discussionsupporting
confidence: 89%
“…Proteinaceous casts, tubular necrosis, and medullary congestion are established histologic features of ischemic AKI. 1,2,18,19 Histologic analyses revealed that Klf4 deletion significantly exacerbated the formation of proteinaceous casts and tubular necrosis and the degree of medullary congestion in response to I/R injury ( Figure 3). These results suggest that endothelial Klf4 plays a protective role in ischemic AKI.…”
Section: Endothelial Klf4 Deletion Exacerbated Renal I/r Injurymentioning
confidence: 99%
“…Histologic analyses were performed, as previously described. 18 Immunohistochemistry was performed with antibodies for Klf4, 36 neutrophil (7/4; Abcam, Inc., Cambridge, MA), CD3« (M20; Santa Cruz Biotechnology, Santa Cruz, CA), Ly6c (ER-MP20; Abcam, Inc.), and F4/80 (CI:A3-1; Abcam, Inc.). Staining was visualized by diaminobenzidine, and sections were counterstained by hematoxylin.…”
Section: Histology and Immunohistochemistrymentioning
confidence: 99%
“…Thus, we recently created contrast medium model rats and reported on our investigation of the effectiveness of hydrogen gas inhalation as a preventative for CIAKI. 53 Specifically, we investigated the effect on renal function and renal tissue of hydrogen gas inhalation by rats on administration of contrast medium, as compared to rats who inhaled a control gas. The results indicated that the inhalation of hydrogen gas suppressed the decrease in renal function caused by the administration of contrast medium.…”
Section: Future Directionsmentioning
confidence: 99%